2008
DOI: 10.1002/hep.22379
|View full text |Cite
|
Sign up to set email alerts
|

Selection of high-avidity CD8 T cells correlates with control of hepatitis C virus infection

Abstract: E fficient control of viral infections in various animaland human models depends on a wide array of mechanisms affecting swiftness and strength of antiviral cellular and humoral immune responses. Diversity of such mechanisms is highlighted by analysis of immune responses elicited by hepatitis C virus (HCV) in humans. Control of acute HCV infection correlates with strong, sustained, and broad virus-specific cellular immunity mediated by both CD4 and CD8 T cells. By contrast, HCV persistence has been associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
50
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 33 publications
4
50
1
Order By: Relevance
“…The functional avidity of responding CD8 + effector T cells plays a critical role in determining the efficacy of these cells in vivo, with high avidity an indicator of cells with increased viral clearance capability (3,5,6,28,43,55,61,63). In our previous studies, we found that the avidity of the effector population present at the peak of the response following respiratory infection is not reflective of the initial population of responding cells, with the mature effector population exhibiting significantly low avidity (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The functional avidity of responding CD8 + effector T cells plays a critical role in determining the efficacy of these cells in vivo, with high avidity an indicator of cells with increased viral clearance capability (3,5,6,28,43,55,61,63). In our previous studies, we found that the avidity of the effector population present at the peak of the response following respiratory infection is not reflective of the initial population of responding cells, with the mature effector population exhibiting significantly low avidity (30).…”
Section: Discussionmentioning
confidence: 99%
“…The generation of lower avidity cells at all may seem at odds with studies that have demonstrated the superior efficacy of high avidity cells for viral and tumor clearance (3,5,6,22,28,34,43,55,61,63). We would speculate that this process may allow for the generation of some breadth in the avidity repertoire as a protective mechanism against supraoptimal stimulation mediated death of the population (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection of high-avidity CD8 T cells correlates with control of viral infections and polyfunctional profiles as well as potent virussuppressive activity including HCV (16,17). Notwithstanding the intrinsic superior antiviral activity of higher avidity TCR CD8 T cells, low-avidity TCR polyfunctional CD8 T cells have been suggested to be more fit in providing disease control during chronic virus infection (18) and have been reported to reject tumors and can have less problems regarding immune pathology (19).…”
mentioning
confidence: 99%
“…As with chronic infections, such as HIV and HCV, as well as in cancer, the host may lose (by clonal exhaustion or other apoptotic mechanisms) the effector cells that are most critical for viral or tumor clearance (18). In the case of HCV, the high-avidity T cells have been suggested to control HCV infection (16,17); however, what remains unclear is whether low avidity T cells may contribute to antiviral mechanisms against the HCV-infected cells.…”
mentioning
confidence: 99%